Respuesta :
2x - 3y = 12
- 2x - 2x
-3y = -2x + 12
-3 -3
y = ²/₃x - 4
y - y₁ = m(x - x₁)
y - 6 = -1¹/₂(x - 2)
y - 6 = -1¹/₂(x) + 1¹/₂(2)
y - 6 = -1¹/₂x + 3
+ 6 + 6
y = -1¹/₂x + 9
- 2x - 2x
-3y = -2x + 12
-3 -3
y = ²/₃x - 4
y - y₁ = m(x - x₁)
y - 6 = -1¹/₂(x - 2)
y - 6 = -1¹/₂(x) + 1¹/₂(2)
y - 6 = -1¹/₂x + 3
+ 6 + 6
y = -1¹/₂x + 9
a perpendicular line has a slope equal to the negative reciprocal of the original slope. In this case, the perpendicular line's slope is equal to -1/2. we use the slope intercept general form of y-y1 = m *(x-x1) in which upon substitution, the form becomes y - 6 = -1/2 * ( x-2) ; y = -1/2x + 7